The Great Recession weighted on Portuguese children: A structural equation modeling approach considering eating patterns. Issue 5 (20th October 2021) - Rodrigues, Daniela; Carmo, Ariene; Gama, Augusta; Machado‐Rodrigues, Aristides M.; Nogueira, Helena; Rosado‐Marques, Vítor; Silva, Maria‐Raquel; Padez, Cristina
Abstract: Objectives: Further evidence on how the Great Recession was associated with childhood obesity is needed, particularly when the world is facing a new and severe economic downturn caused by the COVID‐19 pandemic. This study explores: (1) the direct association of the 2008's economic crisis with eating patterns and body mass index (BMI), among children, independently of their socioeconomic status (SES), and (2) the indirect association between the crisis and children's BMI, by using eating patterns as mediators. Methods: A sample of children ( n  = 8472, mean age: 7.17 years old, 50.8% male) was recruited in schools from the cities of Porto, Coimbra and Lisbon, Portugal. Children's height and weight were objectively measured; BMI was calculated. Other data were collected by a parental questionnaire. A structural equation modeling studied the associations between the economic crisis impact, eating patterns, and BMI; model was adjusted for SES. Results: Children in families that reported a greater impact of the economic crisis showed higher consumption of unhealthy food items and lower consumption of healthy foods, regardless of SES. Indirectly, children whose parents scored higher in the economic crisis impact had higher BMI mediated by a higher consumption of cakes/chocolates and lower intake of vegetables/salads. Conclusions: The economic crisis was associated with higher BMI and unhealthy eating patterns. Efforts to promote healthy diets and weight are needed at a population level rather than for specific social classes, particularly in the face of a new economic crisis caused by the COVID‐19 pandemic.